Association between body fat and bone mineral density in non-obese post-menopausal women over 60 years old - Amirhossein Hosseini; Seyed Reza Hosseini; Reza Ghadimi; Ali Bijani (Babol University of Medical Sciences, 2021)
Background: Loss of bone mineral density is one of the most important complications of menopause. The results of studies about the relation between body fat and bone mineral density are controversial. The aim of this study is to determine the association between fat mass and bone mineral density on non-obese post-menopausal elderly women. Methods: This cross-sectional study is a part of the second phase of the AmirKola Health and Ageing Project (AHAP) that has been done on 356 elderly women with BMI of 18.5-30. Bone mineral density (BMD) and total body fat were measured using the Hologic Horizon-WI densitometer. Statistical tests were ANOVA and Pearson's correlation coefficient and P value less than 0.05 was considered significant. Results: The mean age of participants was 70.22±7.34 and the mean age of menopause was 47.68±5.05. Women with highest fat mass, had a greater spine, femur and whole body BMD (p<0.0001). In this study we observed a direct and positive significant correlation between body fat mass and BMD at spine (r=0.308), femur (r=0.420) and whole body (r=0.312) (p<0.0001).  Conclusion: This study showed a positive correlation between fat mass and bone mineral density in all three anatomical sites in post-menopausal women although lean mass had a greater effect on bone mineral density than fat mass. To prevent osteoporosis in post-menopausal women, it is important to target the lean mass more than fat mass.